2005
DOI: 10.1038/nsmb920
|View full text |Cite
|
Sign up to set email alerts
|

A Brownian motor mechanism of translocation and strand separation by hepatitis C virus helicase

Abstract: Helicases translocate along their nucleic acid substrates using the energy of ATP hydrolysis and by changing conformations of their nucleic acid-binding sites. Our goal is to characterize the conformational changes of hepatitis C virus (HCV) helicase at different stages of ATPase cycle and to determine how they lead to translocation. We have reported that ATP binding reduces HCV helicase affinity for nucleic acid. Now we identify the stage of the ATPase cycle responsible for translocation and unwinding. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
161
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(173 citation statements)
references
References 44 publications
9
161
0
2
Order By: Relevance
“…The molecular mechanism underlying RNA unwinding is not yet clear. However, recent kinetic analyses have shown that the enzyme undergoes highly coordinated cycles of fast dsRNA unwinding with high processivity for about 20 nt (23)(24)(25). Thereafter, the enzyme "pauses" and may fall off the template or start a new cycle of duplex unwinding.…”
Section: Components Of the Hcv Replication Complexmentioning
confidence: 99%
“…The molecular mechanism underlying RNA unwinding is not yet clear. However, recent kinetic analyses have shown that the enzyme undergoes highly coordinated cycles of fast dsRNA unwinding with high processivity for about 20 nt (23)(24)(25). Thereafter, the enzyme "pauses" and may fall off the template or start a new cycle of duplex unwinding.…”
Section: Components Of the Hcv Replication Complexmentioning
confidence: 99%
“…These enzymes use the energy of NTP hydrolysis to unwind double-stranded RNA, and NS3 unwinds RNA and DNA homoduplexes and heteroduplexes in a 3፱ to 5፱ direction 25 . The helicase mechanism is not yet fully understood, but recent kinetic analyses show that the NS3 helicase behaves like a ratcheting two-stroke motor 26 and seems to function as a dimer that incrementally rips apart 18-base-pair stretches of substrate RNA 27 . In addition, NS3 helicase activity can be regulated by interactions between the serine protease and helicase domains of NS3 (refs 28, 29), indicating that these two enzyme activities may be somehow coordinated during replication.…”
Section: Dissecting the Structure And Function Of Hcv Ns Proteinsmentioning
confidence: 99%
“…Despite recent progress in the study of these motor proteins (2-4), the physical mechanisms by which they move and catalyze the strand separation are not well understood. Helicase models ranging from a pure Brownian ratchet to a pure power stroke action have been discussed (5)(6)(7)(8), but experimental data to support them for RNA helicases have been lacking. The hepatitis C virus NS3 protein is a superfamily 2, 3Ј to 5Ј RNA helicase (9) known to be essential for virus replication and, thus, an antiviral drug target (10).…”
mentioning
confidence: 99%